Plant- and Marine-Based Phytochemicals for Human Health: Attributes, Potential, and Use - Goyal, Megh Raj; Chauhan, Durgesh Nandini (Innovations in Plant Science for Better Health, 2019)
This new book, Plant- and Marine- Based Phytochemicals for Human Health: Attributes, Potential, and Use , provides insight with scientific evidence on the use of medicinal plants in the treatment of certain diseases. It describes bioactive compounds of marine and plant origin that have been discovered to be advantageous for human health, shedding new light on the potential of phytochemicals on human health and contributing to the ocean of knowledge on phytochemistry and pharmaceutical biology. In addition, the role of plant-based pharmaceuticals is also discussed as an example of innovative uses of plant product. This book addresses the importance of phytochemicals from plants and marine life. It divided in four parts: Bioactive compounds in medicinal plants: status and potential Plant-based pharmaceuticals in human health: review Therapeutic attributes of mushroom, cereal grains, and legumes Innovative use of medicinal plants This compendium will be useful for the students and researchers as well as for industry professionals working in the food, nutraceuticals, and herbal industries.